The Predictive Power of Symptom Experience and Symptoms Management Strategies on Quality of Life among Patients with Chronic Obstructive Pulmonary Disease in Central Chest Institute of Thailand - Ekkamart, Buachompoo; Phaicharoen, Rangsiya; Phetphiphat, Paveekun (Journal of The Royal Thai Army Nurses, 2023)
This study aims to examine the predictive power of the experience of dyspnea, fatigue, insomnia, anxiety, depression, and symptoms management strategies on quality of life among patients with chronic obstructive pulmonary disease (COPD) in Central Chest Institute of Thailand. The sample of 121 COPD patients was simple random sampling selected. Data collection was performed by using a questionnaire composed of 6 parts: 1) demographic data; 2) Dyspnea, Fatigue, and Insomnia; 3) Hospital Anxiety and Depression; 4) Symptom Management, and 5) the Quality of life. The Cronbach’s Alpha Coefficients were .96, .80, .73 and .92 respectively. Data were analyzed by descriptive statistics and stepwise regression analysis. The results were as follows. Predictive variables on quality of life among COPD patients at level 36.4% included dyspnea, anxiety and insomnia of symptom were perceived by β = -.280, β = -.265, and β = -.224 at p < .01. Therefore, nurses should regularly assess the symptoms of dyspnea, insomnia, anxiety, and develop guidelines for symptoms management to promote quality of life among patients with COPD.